The feasibility and advantages of immediate removal of urinary catheter after lobectomy: A prospective randomized trial - Lei Zhang; Xueying Yang; Ye Tian; Qian Yu; Yang Xu; Di Zhou; Zhuo Wu; Xitong Zhao (Wiley, 2021)
Abstract Aim This study aims to evaluate the feasibility and advantages of immediate urinary catheter removal compared with prolonged indwelling catheterization in lung cancer lobectomy. Design This study was designed as a prospective, single‐centre, randomized and open‐label clinical study. Methods People with lung cancer undergoing lobectomy/pneumonectomy were recruited and randomly allocated to two groups. One group had their urinary catheter removed immediately while the other group had it removed 48 hr after surgery. Results No significant difference in the incidence of postoperative urinary retention (POUR) was observed between the two groups. However, the incidence of postoperative catheter‐associated urinary tract infection (CAUTI) in the immediate removal group (6.7%) was lower than the control group (17.2%) (p = .030). Furthermore, the incidence of catheter‐associated emergence agitation (CAEA) in the control group (25.3%) was higher than the immediate removal group (8.9%) (p = .007). The average length of hospital stay of the immediate removal group [6.51(4-11) days] was shorter than the control group [7.20(5-12) days] (p = .002). Immediate removal of urinary catheter appeared to have fewer complications and shorter hospital stay than delayed removal.